2013
DOI: 10.1074/jbc.m112.425504
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 375 Mediates the Signaling Pathway of Corticotropin-releasing Factor (CRF) Regulating Pro-opiomelanocortin (POMC) Expression by Targeting Mitogen-activated Protein Kinase 8

Abstract: Background: MicroRNA 375 (miR-375) is expressed in the pituitary gland, but its functions and the related mechanisms have not been studied. Results: miR-375 mediates the signaling pathway of CRF regulating POMC expression by targeting MAP3K8. Conclusion: miR-375 negatively regulates POMC expression and related hormone secretion. Significance: These new data suggest that miRNAs play important roles in regulating pituitary hormone secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 47 publications
1
57
0
2
Order By: Relevance
“…At first glance this result seems to vary from our observations. However, several studies have reported that miR-375 acts not as a positive regulator of cell proliferation but rather as a negative modulator (24,(34)(35)(36). At least two scenarios could account for this apparent divergence.…”
Section: Discussionmentioning
confidence: 99%
“…At first glance this result seems to vary from our observations. However, several studies have reported that miR-375 acts not as a positive regulator of cell proliferation but rather as a negative modulator (24,(34)(35)(36). At least two scenarios could account for this apparent divergence.…”
Section: Discussionmentioning
confidence: 99%
“…Egy másik tanulmány-ban az egér központi idegrendszerének különböző részeit vizsgálva sikerült agyalapimirigyre specifikus miRNS-eket azonosítani [22]. Amellett, hogy a miRNSeknek az emberben is fontos szerepük van a normál mirigy fejlődésében [19,23,24] és hormontermelésében [25][26][27][28][29][30][31], az elmúlt években egyre több humán vizsgálat támasztja alá azt is, hogy részt vehetnek az adenomák kialakulásában és növekedésében [32][33][34][35].…”
Section: Mirns-expressziós Eltérések Az Agyalapimirigy-daganatokbanunclassified
“…miRNAs are critical regulators in pituitary development, it is reported that mmu-miR-26b targets lymphoid enhancer factor 1 (LEF1), which up-regulates PIT1 and GH expressions [42]. A highly expressed miRNA in the pituitary gland, mmu-miR-375, is reported to regulate the signaling pathway of CRF and POMC expressions by targeting mitogen-activated protein kinase-8 (MAP3K8) [41]. In our previous study, we detected a large number of porcine miRNAs by using a combination of microarray analysis and Solexa sequencing [21], and differentially expressed miRNAs after GNRH treatment were revealed by miRNA microarray [39].…”
Section: Introductionmentioning
confidence: 99%